Modification of inverse auger hole method for saturated hydraulic conductivity measurement - OJHA, ROHIT PRATAP; VERMA, C. L.; DENIS, DERRICK M.; SINGH, C. S.; KUMAR, MANJUL (Journal of Soil and Water Conservation, 2020)
Saturated hydraulic conductivity of soil is required for designing sub-surface horizontal drainage systems, irrigation systems, ground water abstraction strutures and recharge systems. Available mathematical equation for calculation of saturated hydraulic conductivity assumes flat circular bottom of auger hole but auger used for making hole in soil makes a hemispherical cavity at the bottom of hole. Existing inverse auger hole method was modified for hemispherical bottom. An experiment was conducted to calculate and compare subsurface saturated hydraulic conductivity of uncultivated untilled sodic soil by making an auger hole of 13.0 cm diameter up to 50 cm depth. The average value of saturated hydraulic conductivity measured with existing model was 1.38 cm/ day while with modified equation it was 1.29 cm/day. The value calculated by existing model is 6.5% higher than value obtained using modified model. Saturated hydraulic conductivity of uncultivated untilled sodic soil is quite low hence the difference is not very high but for normal conditions there may be sizable difference. The modified model is based on logically the soundest hypothesis compared to the existing model hence recommended for further field application.